In-vitro Antibacterial Activity of Allium sativum on Common Food Poisoning Bacteria - Ssemwanga, Elastus; Mulungi, Priscillah N.; Tumusiime, Jazira; Dhihume, Willy; Arinaitwe, Bruce; Rugera, Simon Peter; Omara, Denis (Journal of Advances in Microbiology, 2022)
The use of herbal medicines for food poisoning in inadequate resource countries has greatly increased with the limited establishment of antibacterial activity. This study aimed at establishing the antibacterial activity of the aqueous Allium sativum extract against Staphylococcus aureus, Escherichia coli and Salmonella typhimurium. Allium sativum L. (Amaryllidaceae) was purchased from a farmer in Kasese District and was authenticated. The material was then extracted using distilled water, filtered and lyophilized. Evaluation of the phytochemicals in the extract was done using standard procedures. High-Performance Liquid Chromatography (HPLC) fingerprint of the extract was conducted to monitor the reproducibility of the extract. The antibacterial activity of the aqueous garlic extract against the organisms above was evaluated and expressed as Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Phytochemical screening of the garlic extract showed the presence of amino acids, alkaloids, glycosides and saponins, flavonoids, steroids and terpenoids. HPLC fingerprints showed 39 and 98 peaks at 220nm and 254nm wavelengths respectively and the presence of various phytochemical compounds in A. sativum. The extract showed antibacterial activity against S. aureus, E. coli and S. typhi. The aqueous garlic extract exhibited antibacterial activity against tested common food poisoning bacteria, with a high potency against gram-positive bacteria.
Keywords: Allium sativum; antibacterial; food poisoning; Staphylococcus aureus; Escherichia coli; Salmonella typhimurium.